Pelatinan Penggunaa Digital Children's Literature StoryBookScanada. Bagi Siswa EFL SMAN 5 Padang - Leni Marlina; Zul Amri; Dian Safitri; Abelia Rivanka Andricos (Universitas Muhammadiyah Palembang, 2024)
This community service program was conducted at SMA Negeri 5 Padang which is located at Jl. Balai Baru, Kuranji District, Padang City. Two things that become problems for students of SMAN 5 Padang, especially the English Specialization class XI Phase F1 are low motivation and high anxiety in reading English reading. The purpose of this service activity is to increase reading motivation and reduce reading anxiety levels through the use of Digital Children's Literature or digital children's literature on storybookscanada.ca. Pre-test and Post-test were conducted to determine the level of motivation and anxiety in reading in the training participants. Then 10 selected stories from storybookscanada.ca with 20 total parts were used as interactive training media for learners to increase motivation and reduce reading anxiety. After the training, there was an increase of 8.82% for reading motivation and a decrease of 11.92% for reading anxiety. In other words, the training conducted by the Community Service Team (PKM) of Universitas Negeri Padang succeeded in having a positive influence with the results of a significant increase in reading motivation and a decrease in reading anxiety of students in class 11 Phase F1 SMAN 5 Padang.